2007
DOI: 10.3346/jkms.2007.22.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Genes Response in Endothelial Cells Following Hantaan Virus Infection

Abstract: The regulation mechanism of interferon (IFN) and IFN-stimulated genes is a very complex procedure and is dependent on cell types and virus species. We observed molecular changes related to anti-viral responses in endothelial cells during Hantaan virus (HTNV) infection. We found that there are two patterns of gene expression, the first pattern of gene expression being characterized by early induction and short action, as in that of type I IFNs,' and the other being characterized by delayed induction and long du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Binding of IFN-α2 to its receptor initiates a signaling cascade that leads to an increase in the expression of many downstream signaling targets called interferon-stimulated genes [43]. The products of these genes may play a critical role in inhibition of viral spread into non-infected cells and interference of viral replication in the infected cells [44]. IFNγ, on the other hand, is known to mediate its effect via the JAK-STAT signaling pathway leading to the subsequent activation of macrophages and NK cells, and expression of specific major histocompatibility complex proteins [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Binding of IFN-α2 to its receptor initiates a signaling cascade that leads to an increase in the expression of many downstream signaling targets called interferon-stimulated genes [43]. The products of these genes may play a critical role in inhibition of viral spread into non-infected cells and interference of viral replication in the infected cells [44]. IFNγ, on the other hand, is known to mediate its effect via the JAK-STAT signaling pathway leading to the subsequent activation of macrophages and NK cells, and expression of specific major histocompatibility complex proteins [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…After infection of human lung microvascular endothelial cells with either HTNV or SNV at a low MOI of 0.1, no virus‐specific modulation of either cellular adhesion molecules or HLA molecules was found (206). In contrast, after hantavirus infection with a MOI of 1, a strong upreglation of HLA class I molecules on endothelial cells was observed (228, 230, 231) (Fig. 2).…”
Section: Immune Response To Hantaviruses In Humansmentioning
confidence: 92%
“…By using RNA-Seq data, Sang et al found that porcine IRF1 was highly stimulated in M1-IFN γ and M1-LPS statuses while IRF8 was only observed in M1-IFN-γ status [22]. Research analysis of interferon-stimulated genes response in endothelial cells during hantaan virus infection found two patterns of gene expression: the first pattern was identified by early induction and short action, such as type I IFNs; the other was characterized as IRF-7, MxA and TAP-1/2 by delayed induction and long duration [44]. Our data analysis showed that IRF-3 was highly stimulated at 8 hpi and then decreased gradually.…”
Section: The Expression Of Interleukin and Ifn-related Gene Upon The mentioning
confidence: 99%